Notch and PKC Are Involved in Formation of the Lateral Region of the Dorso-Ventral Axis in Drosophila Embryos. - Tremmel, D.M.; Resad, S.; Little, C.J.; Wesley, C.S. (PLoS ONE, 2013)
The Notch gene encodes an evolutionarily conserved cell surface receptor that generates regulatory signals based on interactions between neighboring cells. In Drosophila embryos it is normally expressed at a low level due to strong negative regulation. When this negative regulation is abrogated neurogenesis in the ventral region is suppressed, the development of lateral epidermis is severely disrupted, and the dorsal aminoserosa is expanded. Of these phenotypes only the anti-neurogenic phenotype could be linked to excess canonical Notch signaling. The other phenotypes were linked to high levels of Notch protein expression at the surface of cells in the lateral regions indicating that a non-canonical Notch signaling activity normally functions in these regions. Results of our studies reported here provide evidence. They show that Notch activities are inextricably linked to that of Pkc98E, the homolog of mammalian PKC?. Notch and Pkc98E up-regulate the levels of the phosphorylated form of I?BCactus, a negative regulator of Toll signaling, and Mothers against dpp (MAD), an effector of Dpp signaling. Our data suggest that in the lateral regions of the Drosophila embryos Notch activity, in conjunction with Pkc98E activity, is used to form the slopes of the opposing gradients of Toll and Dpp signaling that specify cell fates along the dorso-ventral axis.